In Vitro Investigation of HIF-1α as a Therapeutic Target for Thyroid-Associated Ophthalmopathy - Lee, Jeongmin; Lee, Jinsoo; Baek, Hansang; Lim, Dong-Jun; Lee, Seong-Beom; Lee, Jung-Min; Jang, Sang-Ah; Kang, Moo Il; Yang, Suk-Woo; Kim, Min-Hee (Endocrinology and metabolism (Seoul), 2024)
Background: Thyroid-associated ophthalmopathy (TAO) involves tissue expansion and inflammation, potentially causing a hypoxic microenvironment. Hypoxia-inducible factor (HIF)-1α is crucial in fibrosis and adipogenesis, which are observed in TAO progression. We investigated the effects of hypoxia on orbital fibroblasts (OFs) in TAO, focusing on the role of HIF-1α in TAO progression.Methods: OFs were isolated from TAO and non-TAO patients (as controls). In addition to HIF-1α, adipogenic differentiation markers including peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer binding protein (CEBP) were measured by Western blot, and phenotype changes were evaluated by Oil Red O staining under both normoxia and hypoxia. To elucidate the effect of HIF-1α inhibition, protein expression changes after HIF-1α inhibitor treatment were evaluated under normoxia and hypoxia.Results: TAO OFs exhibited significantly higher HIF-1α expression than non-TAO OFs, and the difference was more distinct under hypoxia than under normoxia. Oil Red O staining showed that adipogenic differentiation of TAO OFs was prominent under hypoxia. Hypoxic conditions increased the expression of adipogenic markers, namely PPARγ and CEBP, as well as HIF-1α in TAO OFs. Interleukin 6 levels also increased in response to hypoxia. The effect of hypoxia on adipogenesis was reduced at the protein level after HIF-1α inhibitor treatment, and this inhibitory effect was sustained even with IGF-1 stimulation in addition to hypoxia.Conclusion: Hypoxia induces tissue remodeling in TAO by stimulating adipogenesis through HIF-1α activation. These data could provide insights into new treatment strategies and the mechanisms of adipose tissue remodeling in TAO.